PERAN TATA KELOLA LAYANAN BIMBINGAN DAN KONSELING BAGI SISWA DI SEKOLAH - Ronny Gunawan (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
Guidance and Counseling in schools is a service that is held as one of the support of teaching and learning activities in schools. In its day-to-day activities guidance and counseling is organized by Guidance and Counseling teachers to implement four areas of counseling, counseling services, support activities that all can assist students in learning in school and living everyday life as learners. Based on its activities a Guidance and Counseling teacher needs to master the governance of Guidance and Counseling services in school, because a teacher Guidance and Counseling is a manager and implementer of every Guidance and Counseling service in school. Guidance and Counseling Teachers should be able to design Guidance and Counseling programs, make measurements, archive all counseling data relating to students to the evaluation. All such activities are called governance of Guidance and Counseling services in schools. Thus a Guidance and Counseling teacher has a significant role in governance of counseling and guidance services for students at school. A significant role of teachers Guidance and Counseling can help students in developing personality and ultimately students can plan their future according to capabilities possessed. Keywords: guidance and counseling, management, service, school, students